Finite Field Metrics Applied to M-Fsk Modulation in Vlc Systems - Soto-Gomez, J; San Juan-Urrutia, E; Adasme-Soto, P; Guajardo-Penroz, C (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper provides an alternative to digital filter based frequency detection for multi-frequency shift keying modulation (M-FSK) using field programmable gate array (FPGA) architectures, by providing a hamming space autocorrelation based detector that outperforms the use of digital filters by consuming only 4% of an equivalent filter s logic resources and no DSP blocks at all, with a detection accuracy of 97% while being non-dependant on Hermitian symmetry or any other radio frequency (RF) signal condition. This detection method supports an inexpensive, reliable and accurate real time data demodulation strategy for flicker-free, high dimming range visible light communications (VLC) multi-user systems. © 2020 IEEE.